1820 N.H. Laws 907 - (:unkn) unknown (My University, 1820)
An Act to Provide for the Appointment of Inspectors and Regulating the Manufacture of Gunpowder, ch. 24, §§ 1-9: Authorized the creation of "inspector of gunpowder" for public powder magazines and powder manufactories. Required gun powder manufactured in the state to be composed of certain qty/quality of materials. Authorized inspection of gunpowder. Bans sale of gunpowder not up to standards.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER